Graphene oxide‐enhanced polyethersulfone/polysulfone forward osmosis membranes for Suez Canal water desalination - Hassan, Mai A.; Hamdy, Gehad; Taher, F. A.; Ali, Sahar S.; Sabry, Rania M. (Polymer engineering and science, 2024)
Forward osmosis (FO) has emerged as a highly promising and energy‐efficient technology for seawater desalination. This study investigates the enhancement of polyethersulfone/polysulfone FO membranes by incorporating graphene oxide (GO) for seawater desalination. The effects of different GO concentrations on membrane properties and FO desalination performance were examined. Among the tested membranes, the one with 0.04 wt% GO exhibited optimal hydrophilicity, as indicated by a lower contact angle (53.93° ± 5.61°), higher porosity (69.86 ± 0.66), and a minimal structure parameter (312.33 μm). The GO.04 membrane demonstrated significantly improved water flux (Jw) of 106 L/m2 h and low reverse salt flux (Js) of 0.69 g/m2 h. Compared to the GO0 membrane without GO, the water flux was 103% higher without compromising salt selectivity (Js/Jw = 0.0065 g/L) when using distilled water as the feed solution (FS) and 1 M NaCl as the draw solution. However, over a threshold of 0.09%, GO concentration on membrane surfaces and pores can impede water flow, reducing porosity and increasing resistance to membrane transport. The GO.04 membranes also exhibited high water flux (113, 94.28, and 84.64 L/m2 h) when brackish water with different NaCl concentrations (5000, 10,000, and 15,000 mg/L) was used as the FS. Moreover, under real seawater conditions from the Suez Canal, the GO.04 FO membrane showed a significantly higher water flux of 94.3 L/m2 h. These findings provide valuable insights into the desalination of actual seawater from the Suez Canal, offering significant potential for the advancement of water treatment and resource management practices. GO‐blended PES/PSF FO membrane performance for suez canal water desalination.